Internal Control Systems and Local Government Financial Performance: The Mediating Effects of Accountability and Transparency - Roni Roni; Mattalatta Mattalatta; Andi Hidayat (Vifada Management and Digital Business, 2025)
The purpose of this study is to analyze the effect of internal control systems on accountability, transparency, and local government financial performance in Mamuju Regency, West Sulawesi Province. In addition, this study aims to examine the effect of accountability and transparency on local government financial performance, as well as to analyze the indirect effect of internal control systems on financial performance through accountability and transparency. This study employs a quantitative approach, with data collected through a questionnaire. The sample consists of 107 civil servants (ASN) in Mamuju Regency, West Sulawesi Province, who are directly involved in regional financial management, including those working in the Regional Financial and Asset Management Agency (BPKAD), Inspectorate, and other local government agencies (OPD). Statistical analysis was conducted using SPSS software with path analysis, and the Sobel test was applied to examine mediation effects. The results of the study indicate that: (1) internal control systems have a positive and significant effect on accountability in Mamuju Regency, West Sulawesi Province; (2) internal control systems have a positive and significant effect on transparency; (3) internal control systems have a positive and significant effect on local government financial performance; (4) accountability has a positive and significant effect on local government financial performance; (5) transparency has a positive and significant effect on local government financial performance; (6) internal control systems have a positive and significant indirect effect on financial performance through accountability; and (7) internal control systems have a positive and significant indirect effect on financial performance through transparency.